Challenges on the Practical Use of Augmented Reality by Non-technical Users: A Case Study - de Sousa, Igor Oliveira; Costa, Thiago Jansen Sampaio; Malheiros, Marcelo de Gomensoro; Bicho, Alessandro de Lima (Anais do Simpósio de Realidade Virtual e Aumentada (SVR); 2023: Anais do XXV Simpósio de Realidade Virtual e Aumentada, 2023)
We describe an experiment to assess the ease of use of Augmented Reality tools and techniques by end-users. We are particularly interested in the user-facing limitations of current AR technologies, both from the device and operating system support of open standards and from specific low-complexity tasks that users must perform to publish and consume AR content. For this, we design and implement a simple e-commerce architecture, where two user profiles interact, a retailer and a customer. A store-like platform is created for registering and publishing web-based 3D models by retailers. Customers then access this platform through smartphones, selecting and interacting with 3D content through markerless AR. We examine a small set of technologies in this particular context, briefly covering platform APIs and interoperable storage formats. We realize that there are still gaps in the content-consumption pipeline for AR that hampers straightforward usage by end-users. Moreover, even when choosing the simplest standards and widest available tools, we still notice device limitations and hardware incompatibilities. For evaluation, we discuss our human interface protocol, which shows that most users have no problems understanding AR interaction or perceiving the added value of this medium. Yet, users struggle with technical and interoperability issues, most of them outside of the scope of Augmented Reality techniques.